The Influence of Motivation, Career Development, and Compensation on Job Satisfaction and its impact on the Employee Performance - Edi Komara (STIE Indonesia Banking School, 2023)
This study aims to examine the influence of motivation, career development and compensation, on job satisfaction and its impact on the employee performance. The independent variables in this study are motivation, career development and compensation. While the related variables in this study are job satisfaction and employee performance. This research was conducted at PT. X at Jl. Bangka Raya, Jakarta Selatan. The sample in this study used 45 employees of PT. X and the method used is Partial Least Square (PLS). the result of this study showed that: 1) motivation has a positive effect on job satisfaction, 2) motivation has a positive effect on employee performance, 3) career development has a positive effect on job satisfaction, 4) career development has a positive effect on employee performance, 5) compensation has a positive effect on job satisfaction, 6) compensation has a positive effect on employee performance, 7) job satisfaction has a positive effect on employee performance, 8) Motivation mediates the influence of Employee Performance through Job Satisfaction, 9) career development mediates the influence of employee performance through job satisfaction, and 10) compensation mediates the influence of employee performance through job satisfaction.